(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe the clinical and paraclinical characteristics of patients with soft tissue defects due to trauma. To evaluate the outcomes of skin graft surgery in the treatment of post-traumatic soft tissue defects at the Department of Plastic and Aesthetic Surgery, Hanoi Medical University Hospital, in 2024. Subjects and Methods: A prospective, descriptive, non-controlled study was conducted on 99 patients with soft tissue defects resulting from traffic accidents, occupational injuries, or domestic accidents. All patients underwent autologous skin grafting at the Department of Plastic and Aesthetic Surgery between June and December 2024. Data were collected from medical records and postoperative follow-up and analyzed using descriptive statistical methods. Results: Patients aged 20–60 accounted for the highest proportion (54.55%), with males representing 53.54%. The most common cause of injury was traffic accidents (59.6%). The most frequently affected sites were the foot (44.4%) and the lower leg (34.3%). Split-thickness skin grafts were more commonly used (60.61%). The reasonable graft survival rate was 91.92%, and wound healing mainly occurred within 8–12 days (66.67%). The complication rate was low (7.07%). After 3 months, 61.62% of patients had normal sensation at the graft site, and 62.63% had limited joint mobility. Conclusion: Autologous skin grafting is an effective method for treating post-traumatic soft tissue defects, demonstrating a high graft survival rate, short healing time, and relatively good functional recovery. The findings support the improvement of clinical treatment protocols in plastic surgery departments.